A Comparative Evaluation of a Parent-Training Program –Republished Article. Issue 6 (November 2016) - Patterson, Gerald R.; Chamberlain, Patricia; Reid, John B.
Abstract: This report is one of a series of outcome evaluation studies for parent-training procedures tailored specifically to families of preadolescent antisocial children. Referred families were screened to identify 19 problem children who were observed in their homes to be high-rate social aggressors. Cases were randomly assigned to the parent-training procedures or to a waiting-list comparison group. All but one of the latter accepted a referral for treatment elsewhere in the community. After an average of 17 hours of therapy time, the cases in the experimental group were terminated. Posttreatment observation data were collected in the homes of both the experimental and the comparison groups. The results indicated that, relative to the changes in the comparison sample, the parent-training sample showed a significantly greater reduction in the observed rates of deviant child behavior.